Synergistic Pro-Apoptotic Effect of a Cyclic RGD Peptide-Conjugated Magnetic Mesoporous Therapeutic Nanosystem on Hepatocellular Carcinoma HepG2 Cells - Xuanping Zhao; Chuan Liu; Zichao Wang; Yingyuan Zhao; Xuyang Chen; Haizhen Tao; Hong Chen; Xueqin Wang; Shaofeng Duan (Pharmaceutics, 2023)
Numerous nanocarriers have been developed to deliver drugs for the treatment of hepatocellular carcinoma. However, the lack of specific targeting ability, the low administration efficiency, and insufficient absorption by hepatocellular carcinoma cells, severely limits the therapeutic effect of the current drugs. Therefore, it is still of great clinical significance to develop highly efficient therapies with few side effects for the treatment of hepatocellular carcinoma. Herein, we developed a highly effective nanocarrier, cyclic RGD peptide-conjugated magnetic mesoporous nanoparticles (RGDSPIO@MSN NPs), to deliver the chemotherapeutic drug doxorubicin (DOX) to human hepatocellular carcinoma HepG2 cells, and further explored their synergistic apoptosis-promoting effects. The results showed that the prepared RGDSPIO@MSN NPs had good stability, biosafety and drug-loading capacity, and significantly improved the absorption of DOX by HepG2 cells, and that the RGDSPIO@MSN@DOX NPs could synergistically promote the apoptosis of HepG2 cells. Thus, this cyclic RGD peptide-modified magnetic mesoporous silicon therapeutic nanosystem can be regarded as a potentially effective strategy for the targeted treatment of hepatocellular carcinoma.